The Dynamics of A Square Root Prey-Predator Model with Fear - Fakhry, Nabaa Hassain; Naji, Raid Kamel (Iraqi Journal of Science, 2020)
An ecological model consisting of prey-predator system involving the prey’s fear is proposed and studied. It is assumed that the predator species consumed the prey according to prey square root type of functional response. The existence, uniqueness and boundedness of the solution are examined. All the possible equilibrium points are determined. The stability analysis of these points is investigated along with the persistence of the system. The local bifurcation analysis is carried out. Finally, this paper is ended with a numerical simulation to understand the global dynamics of the system.